Alternatives to Imprisonment as an Effort to Overcome Overcrowding in Correctional Institutions - Pudjiastuti, Diah; Ravena, Dey; Zakaria, Chepi Ali Firman (Sekolah Tinggi Hukum Bandung, 2025)
The high crime rate and overcapacity in correctional institutions underscore the necessity of examining the effectiveness of prison sentences and exploring fairer alternative sanctions. This research aims to analyze the effectiveness of prison sentences within the criminal justice system and identify ideal criminal sanctions to achieve justice. The study employs a normative juridical method with a descriptive approach. The findings reveal that prison sentences carry negative consequences, including stigmatization and challenges in social reintegration. To enhance the effectiveness of law enforcement and realize justice, the study recommends adopting restorative justice approaches, strengthening preventive measures, and integrating non-legal considerations into law enforcement. Thus, this research contributes to shaping criminal law policies that are not solely repressive but also preventive and rehabilitative. It advocates for the development of a legal system adaptable to the challenges of overcapacity in correctional institutions, promoting a balance between repression, prevention, and rehabilitation for a more equitable and sustainable justice framework.